Human Cytomegalovirus Up-Regulates Endothelin Receptor Type B: Implication for Vasculopathies?. (24th December 2015) - Yaiw, Koon-Chu; Mohammad, Abdul-Aleem; Costa, Helena; Taher, Chato; Badrnya, Sigrun; Assinger, Alice; Wilhelmi, Vanessa; Ananthaseshan, Sharan; Estekizadeh, Atosa; Davoudi, Belghis; Ovchinnikova, Olga; Shlyakhto, Eugene; et al.
Abstract: Background.  Both endothelin receptor type B ([ETB R], a G protein-coupled receptor that mediates the vascular effects of the potent vasoconstrictor endothelin-1) and human cytomegalovirus ([HCMV], a ubiquitous herpesvirus) have been implicated in the pathogenesis of cardiovascular disease (CVD). The effects of HCMV infection on ETB R expression are unknown. We hypothesized that HCMV may contribute to the pathogenesis of CVD via ETB R modulation. Methods.  Human CMV effects on ETB R were studied in vitro in endothelial cells (ECs) and smooth muscle cells (SMCs) and ex vivo in human carotid plaque tissue specimens. Expression of ETB R and viral immediate-early were quantified using quantitative polymerase chain reaction. Functional consequences after ETB R blockade in ECs were examined by 3-[4, 5-dimethylthiazol-2-yl]-2, 5-diphenyl tetrazolium bromide proliferation, wound healing, tube formation, and flow adhesion assays. Results.  Human CMV is capable of upregulating both ETB R mRNA and protein expression in ECs and SMCs. The ETB R was also abundantly expressed in ECs, foam cells, and SMCs, and, more importantly, in HCMV-positive cells in human carotid plaques. Endothelin receptor type B blockade led to decreased proliferation and reduced tumor necrosis factor α-mediated leukocyte recruitment in both uninfected and HCMV-infected ECs. Direct HCMV infection was antimigratory and antiangiogenic in ECs. Conclusions.  Human CMV may contribute to CVD via ETB R induction.